Ablation-resistant glass fiber reinforced nylon material
By using anti-ablation additive system and biodegradable polyester in ablation-resistant glass fiber reinforced nylon materials, combined with specific process conditions, the complex problems of easy consumption and recycling of materials at high temperatures are solved, high-temperature thermal stability and degradability are achieved, manufacturing costs are reduced and the filling effect of composite materials is improved.
Patent Information
- Application Number
- CN202411656743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing ablation-resistant glass fiber reinforced nylon materials are easily consumed at high temperatures. The exposure of glass fibers during processing is dangerous, the manufacturing cost is high and the recycling and processing is complex, so it is impossible to achieve high temperature thermal stability, uniform filling of mold cavity, equivalent low-cost replacement of raw materials and material degradability.
The anti-ablation additive system is adopted, including phenolic resin, boride and silicon carbide powder. Through specific preparation processes and process conditions, biodegradable polyester and calcium sulfate whiskers are combined to optimize the combination and processing technology of nylon and glass fiber to achieve high temperature thermal stability and degradability of the material.
It improves the high-temperature thermal stability of the material, avoids exposure of glass fiber, reduces manufacturing costs, simplifies recycling and processing, and realizes the degradability of the material and efficient composite filling.
Smart Images

Figure CN119505526A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ablation-resistant materials, in particular to an ablation-resistant glass fiber reinforced nylon material. Background Art
[0002] Nylon is a thermoplastic engineering plastic with good mechanical properties, wear resistance, chemical corrosion resistance and self-lubrication. Common nylon varieties include nylon 6, nylon 66, nylon 11, nylon 12, etc. Different varieties of nylon have slightly different properties.
[0003] With the rapid development of modern industry, the demand for high-performance materials is growing. In various fields, such as automobiles, aerospace, electronics and electrical appliances, materials are required to have good mechanical properties, heat resistance and flame retardancy, and also to meet the requirements of lightweight and environmental protection. Glass fiber reinforced nylon material, as a high-performance composite material, just adapts to this development trend. At the same time, people's requirements for product quality and safety are constantly improving, which also prompts material manufacturers to continuously develop materials with better performance. In addition, the concept of sustainable development has been deeply rooted in the hearts of the people, making environmentally friendly materials receive more attention, and glass fiber reinforced nylon materials also have certain advantages in terms of recyclability.
[0004] However, during the processing and use process, the glass fiber may be exposed, affecting the appearance quality of the product and even causing harm to the human body. Moreover, compared with ordinary nylon materials, the cost of glass fiber reinforced nylon materials is higher, which limits its application in some cost-sensitive fields. In addition, the composite structure of glass fiber and nylon makes the recycling of materials relatively complicated, and the current recycling technology is not mature enough.
[0005] Therefore, it is very necessary for the present application to propose an ablation-resistant glass fiber reinforced nylon material to solve the problems in the background.
[0006] 1. Patent document CN112759929B discloses a high-rigidity glass fiber reinforced flame-retardant and wear-resistant nylon material. The above patent realizes a mixed nylon resin of 33.5%-43.5%, glass fiber of 20%-40%, metal sulfide of 5%-10%; halogen-free flame retardant of 15%-20%, compatibilizer of 1%-3%, and processing aid of 1.0%-2%. The mixed nylon resin is a mixture of polyamide MXD6 and PA66 resin in a weight ratio of 25:8.5-18.5, and the halogen-free flame retardant is a phosphorus-nitrogen halogen-free flame retardant. However, the above patent cannot realize the function of high-temperature thermal stability of the material.
[0007] 2. Patent document CN109627758B discloses a halogen-free flame retardant glass fiber reinforced nylon. The above patent realizes a new type of halogen-free flame retardant compound system. The halogen-free flame retardant compound system has low solubility and high charring rate. The prepared halogen-free flame retardant glass fiber reinforced nylon has excellent flame retardant effect and can meet the flame retardant standard of UL94-V0 (1.6mm). However, the above patent cannot achieve uniform filling of the mold cavity with multiple composite materials.
[0008] 3. Patent document CN107236296B discloses nylon glass fiber reinforced alcoholysis resistant material. The above patent realizes that nylon glass fiber reinforced alcoholysis resistant material has excellent alcoholysis resistance, high impact resistance and dimensional stability, and ensures that stress cracking does not occur at the assembly joint. The pressure pulse test of the manufactured product can reach 250,000 times without cracking or leakage, but the above patent cannot achieve equivalent low-cost replacement of raw materials.
[0009] 4. Patent document CN114736511B discloses a low mold fouling, high temperature resistant, halogen-containing flame retardant, reinforced high temperature nylon material and a preparation method thereof. The above patent realizes the use of synthetic phosphorus silicon-modified magnesium hydroxide and calcined shell powder as flame retardant synergists, so that the low mold fouling, high temperature resistant, halogen-containing flame retardant, reinforced high temperature nylon material of the present invention has excellent mechanical properties, flame retardant properties and processability, and the material has good temperature resistance during the processing and produces less mold fouling, but the above patent cannot achieve the degradability of the material.
[0010] In summary, the above patents cannot achieve the functions of high-temperature thermal stability of materials, uniform filling of mold cavities with multiple composite materials, equivalent low-cost replacement of raw materials, and material degradability, resulting in the easy consumption of materials at high temperatures, the danger of glass fiber exposure during processing and production, high manufacturing costs, limited use of space, and relatively complex recycling of glass fiber reinforced nylon materials;
[0011] To this end, the present application proposes an ablation-resistant glass fiber reinforced nylon material that can achieve the functions of high-temperature thermal stability of the material, uniform filling of the mold cavity with multiple composite materials, equivalent low-cost replacement of raw materials and material degradability. Summary of the invention
[0012] The purpose of the present invention is to provide an ablation-resistant glass fiber reinforced nylon material to solve the technical problems proposed in the above-mentioned background technology, such as the inability to realize the functions of high-temperature thermal stability of the material, uniform filling of the mold cavity with multiple composite materials, equivalent low-cost replacement of raw materials and material degradability, which leads to easy consumption of the material at high temperature, danger of glass fiber exposure during processing and production, high manufacturing cost, limited use space and relatively complex recycling and processing of glass fiber reinforced nylon materials.
[0013] To achieve the above object, the present invention provides the following technical solution: an ablation-resistant glass fiber reinforced nylon material, the raw material composition includes, by weight percentage:
[0014] Nylon 30-60%, glass fiber 20-40%, anti-ablation additive system 10-30%;
[0015] The anti-ablation additive system comprises, by weight percentage, 50-70% of phenolic resin, 15-30% of boride, and 5-15% of silicon carbide powder. The phenolic resin is a thermosetting phenolic resin with a molecular weight of 500-1000. The structural formula of the phenolic resin is shown in the following formula (I):
[0016]
[0017] In the structural formula (I), n represents the degree of polymerization, n=5 to 10, and Ar represents the benzene ring and the substituents on the benzene ring;
[0018] The preparation process of the anti-ablation additive system is as follows:
[0019] a. Take a thermosetting phenolic resin, add ethanol to dissolve it, and form a solution with a mass ratio of 1:2 to 1:3;
[0020] b. The boride and silicon carbide powder are mixed in a mass ratio of 1:1 to 2:1, added to the phenolic resin solution obtained in step a, and stirred evenly;
[0021] c. heating the mixed solution to 70-90°C and maintaining it at this temperature for 2-4 hours to allow the phenolic resin and the additive to fully blend to obtain an intermediate product;
[0022] d. Drying the intermediate product at 80-100° C. under reduced pressure to remove the solvent to obtain a finished product of the anti-ablation additive system.
[0023] Preferably, the glass fiber content reaches 30% of the nylon material, and the raw material composition is additionally added with 5-20% biodegradable polyester, 10% toughening agent, 5% antioxidant, and 2% lubricant. The lubricant is Clariant OP wax, and the antioxidant is selected from phenolic antioxidants and aromatic amine antioxidants. The phenolic antioxidant is N, N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, and the aromatic amine antioxidant is selected from N-isopropyl-N'-(dodecylphenyl) p-phenylenediamine. N-isopropyl-N'-(dodecylphenyl) p-phenylenediamine is generated by introducing dodecyl / alkoxy such as ethoxy into the molecular structure of p-phenylenediamine. The toughening agent is selected from at least one of polyolefin, EPDM rubber, thermoplastic polyoctene plastic, ethylene-vinyl acetate copolymer toughening agent and calcium sulfate whisker. The structural formula of ethylene-vinyl acetate copolymer is shown in the following formula (II):
[0024]
[0025] In the structural formula (II), n represents the number of ethylene units, and m represents the number of vinyl acetate units.
[0026] Preferably, the nylon is of modified grade, ester bonds / ether bonds are introduced into the nylon chain, highly hydrophilic components are introduced, the highly hydrophilic components are polyethylene glycol and Tween series, the relative viscosity is 2.75, and the nylon matrix is selected from nylon 6, nylon 66 / nylon 66 copolymer;
[0027] The nylon is dried in a 110°C blast drying oven for 4 hours to remove moisture. The dried nylon, biodegradable polyester, chain extender, compatibilizer and lubricant are mixed in a ratio of 5:2:0.6:0.4. The mixed mixture is used to fully mix the modified nylon and glass fiber using a twin-screw extruder to make a panel. The temperatures from the feeding section of the extruder to the die are: 100°C, 230°C, 230°C, 235°C, 235°C, 240°C, 240°C, 245°C, 245°C and 250°C, and the rotation speed is 480r / min. The panel is combined with the carbon fiber composite material through a lamination process. The surface of the panel is coated with a heat-resistant protective layer with a thickness of 0.1mm to 0.5mm. The heat-resistant protective layer is sprayed on the panel by a spray gun to spray the mixed ceramic powder and the binder. The sprayed panel is sintered at a high temperature and the coating is tightly attached to the surface of the panel.
[0028] Preferably, the mixture is additionally added with 1.5-3% ethylene glycol, 1-2% deionized water, 0.3-0.5% corrosion inhibitor, 0.2-0.5% phosphate buffer, 0.5-3% mildew inhibitor and 0.5-2% plasticizer, the corrosion inhibitor is sarcosine, the mildew inhibitor is natamycin, natamycin is a biological mildew inhibitor, and the phosphate buffer is potassium dihydrogen phosphate and dipotassium hydrogen phosphate;
[0029] The boride is selected from at least one of zinc borate and magnesium borate;
[0030] The mixture undergoes an injection molding process, and the injection molding temperature is controlled between 250°C and 280°C. The linear ablation rate of the material is less than 0.02mm / s at 600°C, and the tensile strength is 100MPa to 150MPa at 23°C.
[0031] Preferably, in step a, the mass ratio of phenolic resin to ethanol is 1:2.0-1:2.5, the intrinsic viscosity is 500-1200cp, and the relative density and melting temperature of polycarbonate are 1.20-1.22g / cm 3 and 220-230℃.
[0032] Preferably, in step b, the mass ratio of boride to silicon carbide powder is 1:1.5 to 1:2.0, the silicon carbide powder is dried to remove moisture, the boride and silicon carbide powder are passed through a ball mill for 30 minutes to 2 hours, the temperature of the mixing process is controlled at 25-75°C, and the stirring is performed by magnetic stirring for 10-15 minutes.
[0033] Preferably, the heating temperature in step c is 80-85° C., the additives include a surfactant and 10% silicon dioxide nanoparticles, the diameter of the silicon dioxide nanoparticles is 35 nanometers, and the surfactant is 8% castor oil polyoxyethylene ether.
[0034] Preferably, the glass fiber is pre-treated with a coupling agent, the coupling agent is selected from a silane coupling agent and a titanate coupling agent, to enhance the bonding force between the glass fiber and the nylon matrix, the glass fiber diameter is 8-14 microns, and the glass fiber length is 2-6 mm;
[0035] The amount of the anti-ablation additive system added is 15-25%. By weight percentage, the raw material composition of the anti-ablation additive system includes: 60-65% phenolic resin; 20-25% boride; 20-40% ceramic powder, 15-30% flame retardant;
[0036] The degree of polymerization of phenolic resin is n=6~8.
[0037] Preferably, the pressure in step d is 10-15 MPa.
[0038] Preferably, the twin-screw extruder is provided with segmented feeding, and 4 sections are allocated to add the mixture, modified nylon and glass fiber at different positions, the modified nylon is added under low shear, the torque is controlled at 50%-80% of the rated torque of the equipment, the torque is gradually increased by 5%-10%, and the side feeder assists the addition of glass fiber when the matrix material has begun to melt, and the length of the high shear zone is reduced by 10%-30%.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention realizes the function of high-temperature thermal stability of the material through the anti-ablation additive system, solves the problem that the material is easily consumed at high temperatures, improves the thermal stability of the material, and makes it difficult to decompose or oxidize at high temperatures;
[0041] 2. The present invention uses a side feeder to achieve uniform filling of the mold cavity with a variety of composite materials, solves the problem of dangerous exposure of glass fibers during processing and production, and improves the utilization rate of glass fibers;
[0042] 3. The present invention uses calcium sulfate whiskers to achieve equivalent low-cost replacement of raw materials, solves the problem of high manufacturing cost and limited use space, reduces material costs, and improves product competitiveness;
[0043] 4. The present invention achieves material degradability through biodegradable polyester, solves the relatively complex problem of recycling and processing of glass fiber reinforced nylon materials, reduces the adverse impact of traditional nylon accumulation on the environment, and is in line with the current theme of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a schematic diagram of the preparation process of the anti-ablation additive system of the present invention;
[0045] Figure 2 This is a schematic diagram of the preparation process of the ablation-resistant glass fiber nylon of the present invention;
[0046] Figure 3 It is a schematic diagram of the tensile performance test and bending performance test results;
[0047] Figure 4 Schematic diagram of ablation rate test results. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] See also Figure 1 and Figure 2 , an embodiment provided by the present invention: an ablation-resistant glass fiber reinforced nylon material, the raw material composition includes, by weight percentage:
[0050] Nylon 30-60%, glass fiber 20-40%, anti-ablation additive system 10-30%;
[0051] The anti-ablation additive system comprises, by weight percentage, 50-70% of phenolic resin, 15-30% of boride, and 5-15% of silicon carbide powder. The phenolic resin is a thermosetting phenolic resin with a molecular weight of 500-1000. The structural formula of the phenolic resin is shown in the following formula (I):
[0052]
[0053] In the structural formula (I), n represents the degree of polymerization, n=5 to 10, and Ar represents the benzene ring and the substituents on the benzene ring;
[0054] The preparation process of the anti-ablation additive system is as follows:
[0055] a. Take a thermosetting phenolic resin, add ethanol to dissolve it, and form a solution with a mass ratio of 1:2 to 1:3;
[0056] b. The boride and silicon carbide powder are mixed in a mass ratio of 1:1 to 2:1, added to the phenolic resin solution obtained in step a, and stirred evenly;
[0057] c. heating the mixed solution to 70-90°C and maintaining it at this temperature for 2-4 hours to allow the phenolic resin and the additive to fully blend to obtain an intermediate product;
[0058] d. drying the intermediate product at 80-100° C. under reduced pressure to remove the solvent to obtain a finished product of the anti-ablation additive system; the amount of the anti-ablation additive system added is 15-25%, and the raw material composition of the anti-ablation additive system includes, by weight percentage: 60-65% phenolic resin; 20-25% boride; 20-40% ceramic powder, 15-30% flame retardant; the degree of polymerization of the phenolic resin is n=6-8;
[0059] Furthermore, the cost of calcium sulfate whiskers is only 1 / 200 to 1 / 300 of that of silicon carbide whiskers.
[0060] In step a, the mass ratio of phenolic resin to ethanol is 1:2.0-1:2.5, the intrinsic viscosity is 500-1200cp, and the relative density and melting temperature of polycarbonate are 1.20-1.22g / cm 3 and 220-230°C; in step b, the mass ratio of boride to silicon carbide powder is 1:1.5-1:2.0, the silicon carbide powder is dried to remove moisture, the boride and silicon carbide powder are passed through a ball mill for 30 minutes to 2 hours, the temperature of the mixing process is controlled at 25-75°C, and the stirring is performed by magnetic stirring for 10-15 minutes; in step c, the heating temperature is 80-85°C, the additives include a surfactant and 10% silicon dioxide nanoparticles, the diameter of the silicon dioxide nanoparticles is 35 nanometers, and the surfactant is 8% castor oil polyoxyethylene ether; the pressure in step d is 10-15MPa.
[0061] See also Figure 1 and Figure 2, an embodiment provided by the present invention: an ablation-resistant glass fiber reinforced nylon material, wherein the glass fiber content reaches 30% of the nylon material, 5-20% of biodegradable polyester, 10% of toughening agent, 5% of antioxidant, and 2% of lubricant are additionally added to the raw material composition, the lubricant is Clariant OP wax, the antioxidant is selected from phenolic antioxidants and aromatic amine antioxidants, the phenolic antioxidant is selected from N, N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, the aromatic amine antioxidant is selected from N-isopropyl-N'-(dodecylphenyl) p-phenylenediamine, N-isopropyl-N'-(dodecylphenyl) p-phenylenediamine is generated by introducing dodecyl / alkoxy such as ethoxy into the molecular structure of p-phenylenediamine, the toughening agent is selected from at least one of polyolefin, EPDM rubber, thermoplastic polyoctene plastic, ethylene-vinyl acetate copolymer toughening agent and calcium sulfate whisker, and the structural formula of ethylene-vinyl acetate copolymer is shown in the following formula (II):
[0062]
[0063] In the structural formula (II), n represents the number of ethylene units, and m represents the number of vinyl acetate units;
[0064] Furthermore, the introduction of glass fiber is intended to increase the rigidity and strength of the material while maintaining the material's light weight. Studies have shown that glass fiber reinforced polymers have excellent mechanical properties and heat resistance, and the addition of biodegradable polyesters is intended to provide environmentally friendly material options and support the biodegradability of the material. Phenolic antioxidants such as N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and aromatic amine antioxidants such as N-isopropyl-N'-(dodecylphenyl)-p-phenylenediamine can prevent oxidative degradation of the material during high-temperature processing and use. The use of lubricant Clariant OP wax effectively reduces friction during material processing and improves the material's machinability and surface finish.
[0065] See also Figure 1 and Figure 2, an embodiment provided by the present invention: an ablation-resistant glass fiber reinforced nylon material, the mixture is additionally added with 1.5-3% ethylene glycol, 1-2% deionized water, 0.3-0.5% corrosion inhibitor, 0.2-0.5% phosphate buffer, 0.5-3% mildew inhibitor and 0.5-2% plasticizer, the corrosion inhibitor is sarcosine, the mildew inhibitor is natamycin, natamycin is a biological mildew inhibitor, the phosphate buffer is potassium dihydrogen phosphate and dipotassium hydrogen phosphate, the boride is selected from zinc borate and magnesium borate At least one, the mixture is subjected to an injection molding process, the injection molding temperature is controlled between 250°C and 280°C, the linear ablation rate of the material is less than 0.02mm / s at 600°C, and the tensile strength is 100MPa to 150MPa at 23°C; the glass fiber is pre-treated with a coupling agent, the coupling agent is selected from a silane coupling agent and a titanate coupling agent, and the bonding force between the glass fiber and the nylon matrix is enhanced, the glass fiber diameter is 8-14 microns, and the glass fiber length is 2-6mm;
[0066] Furthermore, it exhibits a low linear ablation rate (<0.02mm / s) at high temperatures and exhibits excellent mechanical properties (tensile strength 100MPa to 150MPa) at room temperature. The added ethylene glycol and plasticizer improve the flexibility of the material, while the use of phosphate buffer and corrosion inhibitor effectively improves the chemical corrosion resistance of the material. The enhanced bonding between glass fiber and nylon matrix is mainly due to the use of coupling agent, which can significantly improve the overall mechanical properties of the composite material. The nylon matrix glass fiber reinforced composite material achieves excellent high temperature resistance and mechanical properties through reasonable formula design and process condition control.
[0067] See also Figure 1 and Figure 2 , an embodiment provided by the present invention: an ablation-resistant glass fiber reinforced nylon material, the nylon is a modified grade, ester bonds / ether bonds are introduced into the nylon chain, and highly hydrophilic components are introduced, the highly hydrophilic components are polyethylene glycol and Tween series, the relative viscosity is 2.75, and the nylon matrix is selected from nylon 6, nylon 66 / nylon 66 copolymer;
[0068] The nylon was dried in a 110°C blast drying oven for 4 hours to remove moisture. The dried nylon, biodegradable polyester, chain extender, compatibilizer and lubricant were mixed in a ratio of 5:2:0.6:0.4. The mixed mixture was extruded by a twin-screw extruder to fully mix the modified nylon with the glass fiber to produce a panel. The temperatures from the feeding section of the extruder to the die were: 100°C, 230°C, 230°C, 235°C, 235°C, 240°C, 240°C, 245°C, 245°C and 250°C, and the speed was 480r / min. The panel was combined with the carbon fiber composite material through a lamination process, and the surface of the panel was coated with a resistant The heat protection layer has a thickness of 0.1 mm to 0.5 mm. The heat-resistant protection layer is sprayed on the panel by a spray gun with a mixed ceramic powder and a binder. After the sprayed panel is sintered at a high temperature, the coating is tightly attached to the panel surface; the twin-screw extruder is set to feed in sections, and 4 sections are allocated to add the mixture, modified nylon and glass fiber at different positions. The modified nylon is added under low shear, and the torque is controlled at 50%-80% of the rated torque of the equipment. The torque gradually increases by 5%-10%. The side feeder assists the matrix material to add glass fiber when it has begun to melt, and the length of the high shear zone is reduced by 10%-30%;
[0069] Furthermore, nylon-based materials are widely used due to their excellent mechanical properties and chemical stability. However, by introducing ester / ether bonds and highly hydrophilic components (such as polyethylene glycol and Tween series), their performance can be further improved, especially in terms of biodegradability and hydrophilicity. In the above process flow, the performance of modified nylon-based composites was successfully optimized through the fine control of temperature and torque, and the application of a segmented feeding strategy. The added highly hydrophilic components significantly improved the wettability of the material. The uniformity and adhesion of the heat-resistant coating were also effectively improved.
[0070] See also Figure 1 and Figure 2 , an embodiment provided by the present invention: an ablation-resistant glass fiber reinforced nylon material, 60 parts of nylon, 9 parts of glass fiber, 15 parts of an ablation-resistant additive system, 5 parts of biodegradable polyester, 10 parts of a toughening agent, 5 parts of an antioxidant, and 2 parts of a lubricant, passed through a ball mill for 30 minutes to 2 hours, the temperature of the mixing process was controlled at 25-75°C, and the stirring was performed by magnetic stirring for 10-15 minutes. After the mixture was mixed, the modified nylon and the glass fiber were fully mixed by a twin-screw extruder to produce a panel. The temperature from the feeding section of the extruder to the die was 100°C, 230°C, 230°C, 235°C, 235°C, 240°C, 240°C, 245°C, 245°C and 250°C, and the speed was 480r / min;
[0071] Further, tensile performance test: Test standard ISO527, fix the two ends of the sample in the upper and lower clamps of the tensile testing machine respectively, ensure that the axis of the sample coincides with the tensile direction, and control the tensile speed between 1-500mm / min. The testing machine records the change data of force value and displacement (or strain) over time;
[0072] Bending performance test: Test standard ISO178, install the sample on the bending fixture, ensure that the center line of the sample coincides with the center line of the fixture, set the loading speed, span and test mode of the test machine, start the test machine, start applying bending force, and calculate the bending strength, bending modulus and bending strain of the material based on the test data;
[0073] Ablation rate test: Test standard QJ2302-1992, install the sample between the electrodes of the arc heating device, and control the power and temperature of the arc by adjusting the current, voltage and other parameters; during the ablation process, use a thermocouple or other temperature measuring instrument to monitor the temperature change of the sample; after a certain period of ablation, stop heating and measure the ablation of the sample;
[0074] The results of tensile and bending tests are as follows: Figure 3 ; Ablation rate test results are as follows Figure 4 .
[0075] Working principle: phenolic resin is dissolved in ethanol to form a solution, mixed with boride and silicon carbide powder, and stirred evenly. The mixed solution is heated to 70-90°C and maintained for 2-4 hours to form an intermediate product. The intermediate product is dried under reduced pressure at 80-100°C to remove the solvent to obtain an anti-ablation additive. Nylon material and other components are mixed in a twin-screw extruder in a specific proportion, and the temperature gradient is precisely controlled. Method 1 combines the modified nylon sheet with the carbon fiber material through a lamination process and coats it with a heat-resistant protective layer; Method 2 controls the structure of the material through an injection molding process to ensure that the ablation rate and mechanical strength meet the expected requirements. The material exhibits excellent ablation rate (<0.02mm / s) at high temperature (600°C), and the tensile strength reaches 100MPa to 150MPa at room temperature (23°C).
[0076] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An ablation-resistant glass fiber reinforced nylon material, characterized in that: The raw material composition includes, by weight percentage: Nylon 30-60%, glass fiber 20-40%, anti-ablation additive system 10-30%; The anti-ablation additive system comprises, by weight percentage, 50-70% of phenolic resin, 15-30% of boride, and 5-15% of silicon carbide powder. The phenolic resin is a thermosetting phenolic resin with a molecular weight of 500-1000. The structural formula of the phenolic resin is shown in the following formula (I): In the structural formula (I), n represents the degree of polymerization, n=5 to 10, and Ar represents the benzene ring and the substituents on the benzene ring; The preparation process of the anti-ablation additive system is as follows: Step a. Take a thermosetting phenolic resin, add ethanol to dissolve it, and form a solution with a mass ratio of 1:2 to 1:3; Step b. Mix the boride and silicon carbide powder in a mass ratio of 1:1 to 2:1, add to the phenolic resin solution obtained in step a, and stir evenly; Step c. heating the mixed solution to 70 to 90° C. and maintaining the mixed solution at this temperature for 2 to 4 hours to allow the phenolic resin and the additive to be fully fused to obtain an intermediate product; Step d. drying the intermediate product at 80-100° C. under reduced pressure to remove the solvent and obtain a finished product of the anti-ablation additive system.
2. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The glass fiber content reaches 30% of the nylon material, and the raw material composition is additionally added with 5-20% of biodegradable polyester, 10% of toughening agent, 5% of antioxidant, and 2% of lubricant. The lubricant is Clariant OP wax, and the antioxidant is selected from phenolic antioxidants and aromatic amine antioxidants. The phenolic antioxidant is N, N'-bis-(3-(3, 5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, and the aromatic amine antioxidant is N-isopropyl-N'-(dodecylphenyl) p-phenylenediamine. N-isopropyl-N'-(dodecylphenyl) p-phenylenediamine is generated by introducing dodecyl / alkoxy such as ethoxy into the molecular structure of p-phenylenediamine. The toughening agent is selected from at least one of polyolefin, ethylene propylene diene rubber, thermoplastic polyoctene plastic, ethylene-vinyl acetate copolymer toughening agent and calcium sulfate whisker. The structural formula of ethylene-vinyl acetate copolymer is shown in the following formula (II): In the structural formula (II), n represents the number of ethylene units, and m represents the number of vinyl acetate units.
3. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The nylon is of modified grade, and ester bonds / ether bonds are introduced into the nylon chain, and highly hydrophilic components are introduced. The highly hydrophilic components are polyethylene glycol and Tween series, and the relative viscosity is 2.
75. The nylon matrix is selected from nylon 6 and nylon 66 / nylon 66 copolymer; The nylon is dried in a 110°C blast drying oven for 4 hours to remove moisture. The dried nylon, biodegradable polyester, chain extender, compatibilizer and lubricant are mixed in a ratio of 5:2:0.6:0.
4. The mixed mixture is used to fully mix the modified nylon and glass fiber using a twin-screw extruder to make a panel. The temperatures from the feeding section of the extruder to the die are: 100°C, 230°C, 230°C, 235°C, 235°C, 240°C, 240°C, 245°C, 245°C and 250°C, and the rotation speed is 480r / min. The panel is combined with the carbon fiber composite material through a lamination process. The surface of the panel is coated with a heat-resistant protective layer with a thickness of 0.1mm to 0.5mm. The heat-resistant protective layer is sprayed on the panel by a spray gun to spray the mixed ceramic powder and the binder. The sprayed panel is sintered at a high temperature and the coating is tightly attached to the surface of the panel.
4. The ablation-resistant glass fiber reinforced nylon material according to claim 3, characterized in that: The mixture is additionally added with 1.5-3% ethylene glycol, 1-2% deionized water, 0.3-0.5% corrosion inhibitor, 0.2-0.5% phosphate buffer, 0.5-3% mildew inhibitor and 0.5-2% plasticizer, wherein the corrosion inhibitor is sarcosine, the mildew inhibitor is natamycin, which is a biological mildew inhibitor, and the phosphate buffer is potassium dihydrogen phosphate and dipotassium hydrogen phosphate; The boride is selected from at least one of zinc borate and magnesium borate; The mixture undergoes an injection molding process, and the injection molding temperature is controlled between 250°C and 280°C. The linear ablation rate of the material is less than 0.02mm / s at 600°C, and the tensile strength is 100MPa to 150MPa at 23°C.
5. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: In step a, the mass ratio of phenolic resin to ethanol is 1:2.0-1:2.5, the intrinsic viscosity is 500-1200cp, and the relative density and melting temperature of polycarbonate are 1.20-1.22g / cm 3 and 220-230℃.
6. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: In the step b, the mass ratio of boride to silicon carbide powder is 1:1.5 to 1:2.0, the silicon carbide powder is dried to remove moisture, the boride and silicon carbide powder are passed through a ball mill for 30 minutes to 2 hours, the temperature of the mixing process is controlled at 25-75°C, and the stirring is performed by magnetic stirring for 10-15 minutes.
7. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: In the step c, the heating temperature is 80-85° C., the additives include a surfactant and 10% silicon dioxide nanoparticles, the diameter of the silicon dioxide nanoparticles is 35 nanometers, and the surfactant is 8% castor oil polyoxyethylene ether.
8. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The glass fiber is pre-treated with a coupling agent, the coupling agent is selected from a silane coupling agent and a titanate coupling agent, to enhance the bonding force between the glass fiber and the nylon matrix, the glass fiber diameter is 8-14 microns, and the glass fiber length is 2-6 mm; The amount of the anti-ablation additive system added is 15-25%. By weight percentage, the raw material composition of the anti-ablation additive system includes: 60-65% phenolic resin; 20-25% boride; 20-40% ceramic powder, 15-30% flame retardant; The degree of polymerization of phenolic resin is n=6~8.
9. The ablation-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The pressure in step d is 10-15 MPa.
10. The ablation-resistant glass fiber reinforced nylon material according to claim 3, characterized in that: The twin-screw extruder is provided with segmented feeding, and 4 sections are allocated to add the mixture, modified nylon and glass fiber at different positions. The modified nylon is added under low shear, and the torque is controlled at 50%-80% of the rated torque of the equipment. The torque is gradually increased by 5%-10%. The side feeder assists the addition of glass fiber when the matrix material has begun to melt, and the length of the high shear zone is reduced by 10%-30%.
Citation Information
Patent Citations
Nylon glass fiber reinforced alcohol-resistant material
CN107236296B
A halogen-free flame-retardant glass fiber reinforced nylon
CN109627758B
A high-rigidity glass fiber reinforced flame-retardant and wear-resistant nylon material
CN112759929B
A low-fouling, high-temperature resistant, halogenated, flame-retardant, reinforced high-temperature nylon material and its preparation method.
CN114736511B